2009
DOI: 10.1001/jama.2009.1866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tarenflurbil on Cognitive Decline and Activities of Daily Living in Patients With Mild Alzheimer Disease<subtitle>A Randomized Controlled Trial</subtitle>

Abstract: EADING THEORIES ON THE PATHOphysiology of Alzheimer disease (AD) implicate overproduction of amyloid-␤ (A␤), particularly 42 amino acid peptide A␤ 42 . [1][2][3] Compounds modulating ␥-secretase enzyme cleaving ␤-amyloid precursor protein (APP) to release various forms of A␤ are candidates for treatment of AD. One such compound is tarenflurbil (formerly R-flurbiprofen), a selective A␤ 42lowering agent that has been shown in vitro and in vivo to modulate ␥secretase activity and reduce A␤ 42 production in favor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
354
1
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 577 publications
(381 citation statements)
references
References 37 publications
6
354
1
10
Order By: Relevance
“…This trial found no effect on cognition, although with higher dose and patients with mild AD there were small benefits [23]. This encouraged a phase 3 clinical trial in 1600 patients with AD but found no beneficial effects in cognitive function and quality of life [7], which resulted in termination of 2 additional phase 3 trials and further development of this compound. Currently, there are still a few phase 3 clinical trials ongoing for AD targeting Aβ, including the abovementioned gantenerumab and solanezumab, and a β-secretase inhibitor, MK-8931.…”
Section: Clinical Trial Setbacks For Drugs That Target Aβmentioning
confidence: 98%
See 1 more Smart Citation
“…This trial found no effect on cognition, although with higher dose and patients with mild AD there were small benefits [23]. This encouraged a phase 3 clinical trial in 1600 patients with AD but found no beneficial effects in cognitive function and quality of life [7], which resulted in termination of 2 additional phase 3 trials and further development of this compound. Currently, there are still a few phase 3 clinical trials ongoing for AD targeting Aβ, including the abovementioned gantenerumab and solanezumab, and a β-secretase inhibitor, MK-8931.…”
Section: Clinical Trial Setbacks For Drugs That Target Aβmentioning
confidence: 98%
“…Accordingly, Aβ-based therapeutics have been extensively investigated in preclinical models and clinical trials. Most prominently, phase 3 trials have been performed on drugs that lower Aβ by inhibiting its production [7,8] and lowering its levels by immunotherapy [9,10], all of which failed to reach their respective clinical endpoints. There is an urgent need, therefore, for fresh approaches to treat AD.…”
Section: Introductionmentioning
confidence: 99%
“…By way of contrast, for example, a key study assessing the drug tarenflurbil analysed 1649 patients with mild Alzheimer's disease. 15 Obviously, prevention studies may need to be larger with a longer follow up than treatment trials enrolling patients with established Alzheimer's disease. Indeed, the authors of the Cochrane review assessing omega-3 PUFAs called for 'further studies of longer duration'.…”
Section: A Mixed Dietmentioning
confidence: 99%
“…10 Further studies needed A magic bullet for Alzheimer's disease seems as elusive as ever. As the disappointing recent results of clinical studies with tarenflurbil, 15 latrepirdine 16 and bapineuzumab 1 underscore, developing pharmacotherapies for Alzheimer's disease is notoriously difficult. But while there is currently no definitive evidence, it seems premature to rule out that some nutrients might, in particular patients and at specific stages in the disease, improve cognitive performance and perhaps reduce the risk of developing dementia.…”
Section: A Mixed Dietmentioning
confidence: 99%
“…Drugs and vaccines that reached the latter stages of FDA testing, such as tramiprosate, tarenflurbil, bapineuzumab, semagacestat, and AN-1792, often proved exceptionally effective at reducing Aβ burden in the brain, but ultimately failed to demonstrate a significant slowdown in cognitive decline when compared to controls [44][45][46][47][48][49][50][51][52]. Furthermore, the literature reveals that 10-20% of patients with clinically diagnosed AD do not have amyloid pathology at autopsy, and that 15-20% of Aβ-positive PET scans are seen in subjects with no cognitive deficits.…”
Section: Theoretical Basis Of Amyloid Imagingmentioning
confidence: 99%